Hakam Singh's Bt cotton triumph: Pests conquered, yields soared - Singh, Vinay; Singh, Gurdeep; Buttar, Tejbir Singh (Indian Farming, 2025)
In the Malwa region of Punjab, cotton cultivation faces a steep decline due to pest infestations and the increasing shift towards water-intensive crops, exacerbating groundwater depletion @0.50 m per year. Amidst this, Sh. Hakam Singh, a farmer from Bathinda, exemplifies resilience through the adoption of Integrated Pest Management (IPM) practices, which have transformed his Bt-cottoncultivation. Overcoming initial challenges of ineffective pesticide use, he collaborated with Punjab Agricultural University (PAU) and adopted eco-friendly techniques, including SPLAT-PBW for pink bollworm management, yellow sticky traps for whiteflies, and community campaigns against pest carryover. His commitment to scientific methods has significantly enhanced his yields from 8.5 to 10.5 q/acre and improved his benefit-cost ratio from 1.90 to 2.59. Hakam’s efforts extend to educating fellow farmers, supporting scientific pest monitoring, and organizing awareness camps, making him a beacon of sustainable agriculture and inspiring a revival of cotton cultivation in the region.